Low-dose or low-dose-rate ionizing radiation–induced bioeffects in animal models. (27th December 2016) - Tang, Feng Ru; Loke, Weng Keong; Khoo, Boo Cheong
Abstract: Animal experimental studies indicate that acute or chronic low-dose ionizing radiation (LDIR) (≤100 mSv) or low-dose-rate ionizing radiation (LDRIR) (<6 mSv/h) exposures may be harmful. It induces genetic and epigenetic changes and is associated with a range of physiological disturbances that includes altered immune system, abnormal brain development with resultant cognitive impairment, cataractogenesis, abnormal embryonic development, circulatory diseases, weight gain, premature menopause in female animals, tumorigenesis and shortened lifespan. Paternal or prenatal LDIR/LDRIR exposure is associated with reduced fertility and number of live fetuses, and transgenerational genomic aberrations. On the other hand, in some experimental studies, LDIR/LDRIR exposure has also been reported to bring about beneficial effects such as reduction in tumorigenesis, prolonged lifespan and enhanced fertility. The differences in reported effects of LDIR/LDRIR exposure are dependent on animal genetic background (susceptibility), age (prenatal or postnatal days), sex, nature of radiation exposure (i.e. acute, fractionated or chronic radiation exposure), type of radiation, combination of radiation with other toxic agents (such as smoking, pesticides or other chemical toxins) or animal experimental designs. In this review paper, we aimed to update radiation researchers and radiologists on the current progress achieved in understanding the LDIR/LDRIR-induced bionegative and biopositive effects reported in the various animal models. The roles played by a variety of molecules that are implicated in LDIR/LDRIR-induced health effects will be elaborated. The review will help in future investigations of LDIR/LDRIR-induced health effects by providing clues for designing improved animal research models in order to clarify the current controversial/contradictory findings from existing studies.